The role of tumor necrosis factor in the development of cachexia in patients with chemoresistant tuberculosis - Khudyakov, G. V.; Худяков, Геннадій Володимирович (Czech Republic, Karlovy Vary: Skleněný Můstek, 2017)
According to the research of many scientists and WHO tuberculosis is an epidemic disease all over the world these days, especially its drug-resistant version. In general, a dangerous situation for mankind is created by the cases of tuberculosis of MDR and XDR, when they sometimes show greater resistance to anti-tuberculosis drugs, or when the patients have uncorrected side effects. Thus, conditions for the appointment of palliative treatment for these categories of tuberculosis can be formed.